PENGARUH DIGITAL MARKETING, KUALITAS PRODUK, DAN PRICE DISCOUNT TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN PADA DAPUR MUNAWAROH DI SITUBONDO - Deliyana Putri; Riska Ayu Pramesthi; Ediyanto Ediyanto (Fakultas Ekonomi dan Bisnis, 2025)
This study is titled “The Influence of Digital Marketing, Product Quality, and Price Discounts on Repeat Purchase Intentions through Consumer Satisfaction as an Intervening Variable at Dapur Munawaroh in Situbondo.” The purpose of this study is to analyze the extent to which these three variables influence repeat purchase intentions with consumer satisfaction as a mediator. The research method used is quantitative with a survey approach targeting 97 randomly selected consumers of Dapur Munawaroh. Data was analyzed using Smart PLS 3.0 to test validity, reliability, and relationships between variables. The results indicate that product quality has a significant positive influence on consumer satisfaction, while digital marketing directly influences repurchase intention. Additionally, consumer satisfaction was proven to be a key factor in increasing repurchase intention. However, price discounts and digital marketing did not show a significant influence on consumer satisfaction, either directly or indirectly. These findings provide recommendations for Dapur Munawaroh to focus more on maintaining product quality consistency, optimizing digital marketing strategies, and enhancing customer satisfaction to encourage repeat purchases.